Update on functional mitral regurgitation: a comprehensive review - Rodríguez Olivares, René Ricardo (2020)
In recent decades, the advances in the management of functional mitral regurgitation (MR), makes knowledge of this disease extremely important to the clinical cardiologist, as it has an increasing prevalence in patients older than 50 years. The objective of this article is to review the pathophysiological bases of MR, in order to differentiate its mechanism, and to correlate them with the clinical, hemodynamic, and imaging findings that assess the severity of the disease. These data are relevant for the adequate selection of the patient and the opportune moment of the therapeutic interventions, which involves a multidisciplinary team in decision-making to achieve the greatest benefit within the treatment options of this pathology.